217k views
24 votes
If s(x) = 2x2 + 3x - 4, and t(x) = x + 4 then s(x) · t(x) =

A) 2x3 + 11x2 + 8x - 16
B) 2x3 + 5x2 + 16x - 16
C) 3x3 + 7x2 + 8x + 16
D) 3x3 - 11x2 + 16x + 16

User AndreFeijo
by
5.2k points

1 Answer

9 votes

Answer:

A) 2x3 + 11x2 + 8x - 16.

Explanation:

s(x).t(x) = (x + 4)( 2x2 + 3x - 4)

= x(2x2 + 3x - 4) + 4( 2x2 + 3x - 4)

= 2x3 + 3x2 - 4x + 8x2 + 12x - 16

= 2x3 + 11x2 + 8x - 16

User Editha
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.